Hubungan Kepercayaan dan Tradisi Keluarga pada Ibu Menyusui dengan Pemberian ASI Eksklusif di Kelurahan Sidotopo, Semampir, Jawa Timur - Fifin Triana Enita Setyaningsih; Farapti Farapti (Universitas Airlangga, 2018)
Exclusive breastfeeding is one effort made to suppress infant mortality rate. The failure of exclusive breastfeeding practices is closely related to the behavior of breastfeeding. Social culture brings about traditions and beliefs that are often used as guidelines for behavior in the community. Belief has formed into a thing that is beliefed and will be the basis for a person to behave. Tradition is obtained through generations and become individual habits. The purpose of this study is to assess the relationship between exclusive breastfeeding and belief and tradition.This is an analytic research with cross sectional approach. Random sampling technique was used. The population was all breastfeeding mothers who had babies aged 6-12months. The sample obtained were 57respondents. The variables studied were breast feeding mothers’ beliefs and traditions on exclusive breastfeeding. Beliefs about giving complimentary foods to infants and the breastfeeding-related traditions in the community were associated with the implementation of exclusive breastfeeding. Data analysis showed that there was a significant relationship between belief (p value = 0,045) and tradition (p value = 0,019) with exclusive breastfeeding in RW XI of Kelurahan Sidotopo. In conclusion, there is a relationship between belief and tradition in society with practice of exclusive breastfeeding. It is recommended that all sectors address belief and traditions in the effort to support exclusive breastfeeding programs.